ENHANCING MORPHOLOGICAL AWARENESS AND READING FLUENCY IN EFL LEARNERS THROUGH AI TOOLS - Damanik, Lia Agustina; Pratiwi, Resdilla; Rosada, Bintang (Premise: Journal of English Education and Applied Linguistics, 2025)
Morphological awareness, which involves understanding word structure and formation, plays a pivotal role in developing reading fluency among English as a Foreign Language (EFL) learners. This study investigates the effect of AI-based tools on morphological awareness and reading fluency among 25 third-semester English as a Foreign Language (EFL) students at STAIN Mandailing Natal. Using a quantitative pre-test and post-test design, students completed a 30-item morphology awareness test and a fluency reading test before the intervention, which involved using Grammarly and ReadTheory for eight weeks. Grammarly provided feedback on morphology-related errors, while ReadTheory adapted reading passages to proficiency levels. A post-test was used to measure improvements, which were analyzed using a paired t-test. Results show a significant increase in post-test scores, confirming the effectiveness of AI tools in enhancing morphological understanding and reading fluency. Compared to previous studies, this research reinforces the correlation between morphological awareness and reading skills, while highlighting the role of AI as an interactive learning tool. These findings suggest that integrating AI into EFL instruction enhances self-directed learning, improves linguistic accuracy, and fosters reading proficiency.